Development of Secondary Choroidal Neovascularization in Focal Choroidal Excavation of Punctate Inner Choroidopathy. (2nd January 2020) - Haas, Anna-Maria; Stattin, Martin; Ahmed, Daniel; Krebs, Ilse; Ansari-Shahrezaei, Siamak
ABSTRACT: Purpose: To elaborate a case of focal choroidal excavation (FCE) in punctate inner choroidopathy (PIC) complicated by secondary choroidal neovascularization (CNV) based on multimodal imaging findings. Methods: In this retrospective case report, multimodal imaging including near-infrared reflectance, blue peak autofluorescence, spectral domain-optical coherence tomography (OCT), fluorescein and indocyanine green angiography (Heidelberg Engineering GmbH, Germany), and swept source-OCT angiography (SS-OCTA; Topcon Corporation, Japan) was performed. Patients: A 27-year-old moderate myopic woman presented with inactive CNV of unknown origin in her left eye, which had been previously treated with intravitreal anti-vascular endothelial growth factor. Results: Multimodal imaging revealed PIC as the causative disease and systemic corticosteroids were administered. Similar complaints 13 months later showed new CNV formation at the already documented FCE. No sign of PIC could be detected at follow-up. Conclusion: This well-documented case highlighted FCE as the preferential location for CNV development in PIC with multimodal imaging emphasizing a chorioretinal entity. Summary: This case report demonstrated the clinical course of focal choroidal excavation in a patient initially diagnosed with punctate inner choroidopathy complicated by choroidal neovascularization and its treatment response, well documented by multimodal imaging including optical coherence tomography angiography.